2011
DOI: 10.1542/peds.2010-3322
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Outcomes of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Children

Abstract: Mortality rate in children was lower than that reported in adults, but half of affected children suffered long-term complications. The recurrence rate of SJS was high (1 in 5), which suggests vulnerability and potential genetic predisposition. In the absence of standardized management guidelines for these conditions, treatment regimens differed significantly between participating institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
135
1
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 28 publications
17
135
1
15
Order By: Relevance
“…In the study of Finkelstein et al (25) conducted with children, the frequency of sequela was found to be 47% and it was reported that sequelas were most frequently in the form of hypopigmentation of the skin and formation of scar tissue. In our study, sequela changes in the form of wound scar and hyperpigmentation were observed after treatment only in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Finkelstein et al (25) conducted with children, the frequency of sequela was found to be 47% and it was reported that sequelas were most frequently in the form of hypopigmentation of the skin and formation of scar tissue. In our study, sequela changes in the form of wound scar and hyperpigmentation were observed after treatment only in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ferrandiz-Pulido [14,20], late complications occur in approximately 29% of cases and include skin discolouration, nail deformities, chronic ulcerations of the oral cavity and sexual organs, lingual papilla atrophy, photophobia, dry conjunctivitis, conjunctival adhesions, impaired growth of lashes, and blindness. Finkelstein [15] assessed the incidence of late complications at 47%. In the majority of cases, skin discolouration and scars (42%) as well as various types of vision impairment (27%) are observed; the remaining ones include phimosis, bronchitis, cholangitis and venous thrombosis.…”
Section: Treatmentmentioning
confidence: 99%
“…Similar mortality rates in the paediatric population were observed in studies based on case series. According to Spies and colleagues [13] and Ferrandiz-Pulido and colleagues (14), the mortality was 7%; Finkelstein and co-workers [15] found it to be even lower, i.e., 2%.…”
mentioning
confidence: 97%
“…С ССД наиболее часто ассоциируется прием лекарственных препаратов -антиконвульсантов, сульфаниламидов, антибактериальных, нестероид ных противовоспалительных препаратов. В лите ратуре есть указания на возможную связь ССД с ми коплазменной инфекцией, вирусом простого герпеса [4,5]. Y.…”
Section: заметки из практикиunclassified
“…Отдаленные последствия касаются прежде всего по ражения кожи и глаз. Лишь у 1 (2 %) больного сфор мировался облитерирующий бронхиолит [5]. Заин тересованность дистальных отделов респираторного тракта всегда ассоциируется с неблагоприятным прогнозом.…”
Section: заметки из практикиunclassified